Un portrait de Gaignières en creux : l’édition de la correspondance sur Collecta - Elise Vanriest (Les Cahiers de l'École du Louvre)
The transcription and online publication of the correspondence received by Gaignières has been one of the main thrusts of the development of the Collecta website. This important corpus of texts is rich in information that sheds new light on the Gaignières collection and how it was built up. In particular, the correspondence makes it possible to retrace Gaignières’ travels and collecting campaigns. The data extracted from the correspondence also provides input for other areas of research developed by Collecta: geolocation and data visualisation.